PENDIDIKAN ISLAM NON-FORMAL BERBASIS MASJID (PENGALAMAN MASJID AL-FALAH SRAGEN) - Ulfiyatu Ni’mah Afiffah; Mutohharun Jinan (Universitas Muhammadiyah Surakarta, 2021)
The research discusses the function of the Al-Falah Mosque (Masjid Al Falah) Sragen which has many program activities that support its role in developing non-formal Islamic education. This research is included in library research, by data collection using three techniques, namely observation, interviews, and documentation. The analytical method used three steps, namely data reduction, data presentation, and drawing conclusions or verification. Meanwhile, the validity of the data was tested using triangulation of techniques.The role of the Al Falah Mosque in Sragen in the development of non-formal Islamic education was carried out through a program of activities in the field of da'wah and education, namely TPA (Taman Pendidikan Al Qur'an), general studies, special studies for Muslim women, regular studies on Sunday mornings, youth studies, the study of the book of commentaries, Al Falah tutoring, converts to the center, the study of the book of Bulughul Maram, and so on. The driving factors for the Al Falah Great Mosque of Sragen in its role in developing Islamic education are the large quantity of Human Resources (HR), adequate infrastructure, and community enthusiasm and support.